MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) PADA MATA PELAJARAN TEMATIK MUATAN IPS DI MI NW KALIJAGA - Jannah, Nikmatul; Hayaturraiyan, Hayaturraiyan (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Abstract Conventional learning (cermah), is known to have not been able to achieve maximum learning objectives. This can be seen from the low classical learning outcomes of MI NW Kalijaga students, based on the results of pre-cycle data conducted by the researchers, it shows that only 30% of students understand learning well in social studies learning. Classroom action research (CAR), aims to improve the learning process and determine student cognitive learning outcomes after the implementation of the Numbered Head Together (NHT)N Cooperative learning model in the Thematic subjects of Social Sciences (IPS). This research uses a qualitative approach, the type used is Pre-Experimental Design. The subjects of this study were students of class IV B MI NW Kalijaga totaling 24 students consisting of 15 boys and 9 girls. The results obtained during the implementation of this research is an increase in learning outcomes from the data before the implementation of the action. In the first cycle the average value of the class has reached 64 with 53% learning completeness and in the second cycle it has been obtained an increase to an average of 73 with 81% classical learning completeness. The final conclusion that can be conveyed is that the application of the NHT type cooperative learning model can improve learning outcomes.